Desenvolvimento de protocolos de ELISA (enzyme-linked immunosorbent assay) para detecção de proteínas transgênicas CRY2A e VIP3A em milho (Zea mays L.) - Paulino, Willian Elias (2021)
Maize (Zea mays L.) represents an annual crop with high economic and social impact. As it is affected by different pests in the fields, insect-resistant transgenic hybrids were quickly disseminated in the worldwide market. The main proteins responsible for this resistance are the Cry family proteins, such as Cry2a, and the Vip3a protein. To verify the presence and expression of genes or their respective proteins, different methods can be used, ELISA (Enzyme-linked Immunosorbent Assay) is an example. Antibodies used in the assay can be monoclonal or polyclonal. There are different types of ELISA, the most common being the direct ELISA (without capture antibody) and the sandwich ELISA (with capture antibody) to analyze the presence of antigens. The aim of this work was to test and develop a sandwich ELISA protocol using polyclonal antibodies to detect Cry2a expression in corn seeds and a direct ELISA protocol to detect Vip3a protein in transgenic corn seeds and plantlets. Anti-Cry2a polyclonal antibodies were produced and isolated by MyBiosource. Seeds were crushed, roots and shoots were cut from plantlets and buffer solution was added to extract proteins from these tissues. Variation in sample volume, capture antibody concentration, conjugated antibody concentration, substrate volume and specificity for the Cry2a ELISA plate were tested. To assemble the direct ELISA plates for Vip3a, sample volumes from different tissues and applied conjugate volume were tested. The results demonstrated that the sandwich ELISA protocol using polyclonal antibodies was specific and sensible to identify Cry2a expression in maize seeds samples. However, the results for direct ELISA in order to detect Vip3a protein in samples were inconsistent and developing a sandwich ELISA protocol for this protein must be considered too.